Pengaruh Gaya Kepemimpinan dan Team Work Terhadap Kinerja Karyawan di Kopsyah Raya Banda Madani Cabang Curug - Anggun Tri Andini; Meta Juniyanti; Ismatunniami Ismatunniami; Anna Kholifahtul Janah; Riki Gana Suyatna (Jurnal Bintang Manajemen, 2024)
The success of a business unit depends on leadership, teamwork and employee performance. Leadership style and teamwork in leading is very influential and is a determining factor in the ups and downs of employee performance, therefore it is clear that every company needs an effective leadership style and perfect teamwork. The aim of this research is to simultaneously and partially determine the variables of leadership style and team work on employee performance at Kopsyah Raya Banda Madani Curug Branch. The type of data in this research is associative, namely research that asks about the relationship between two variables. The population in this study was all 14 employees. Data collection techniques include interviews with employees and distributing questionnaires to all employees. From the explanation above it can be concluded that the role of leadership and teamwork is important in achieving organizational goals, because in this case apart from depending on the reliability and ability of employees in operating, work units in an organization, leadership effectiveness and the influence and role of leadership are very necessary because in essence success An organization is determined by a good leadership style and teamwork so that it is developed within the organization to achieve organizational goals.